Academische studieprent: oog. - s.n. (s.l. : s.n.)
Lithografie naar rood krijt. Dessiné par Revoil et P. Paté. Scheur in rechter onderhoek.
Herkomst: KASK
kunstwerk
Keywords: Révoil, Pierre; Paté-Desormes, Pierre